Odpowiedzi

2009-11-21T13:20:49+01:00
A) -2*√2(a+√2b)-4(a*√2 - 2b)=
-2×(a√2+b√4)-4a√2+8b=
-2a√2-2b√4-4a√2+8b=-6a√2+6b√4

b) -2*√2(x³+√2x - 2)=
-2√2(x³+√2x+√2b=
-2x³√2-4√x+4√2


c) 3*√2ab²*(-a do piątej √3)=
3√2ab²(-a⁵×√3)
2009-11-21T13:25:57+01:00
A) -2*√2(a+√2b)-4(a*√2 - 2b)=
-2×(a√2+b√4)-4a√2+8b=
-2a√2-2b√4-4a√2+8b=-6a√2+6b√4
b) -2*√2(x³+√2x - 2)=
-2√2(x³+√2x+√2b=
-2x³√2-4√x+4√2
c) 3*√2ab²*(-a do piątej √3)=
3√2ab²(-a⁵×√3)

Myśle że pomogłem :D
Jeśli morzesz daj najlepsza odpowiedz :]
2009-11-21T16:31:05+01:00
A) -2*√2(a+√2b)-4(a*√2 - 2b)=
-2×(a√2+b√4)-4a√2+8b=
-2a√2-2b√4-4a√2+8b=-6a√2+6b√4
b) -2*√2(x³+√2x - 2)=
-2√2(x³+√2x+√2b=
-2x³√2-4√x+4√2
c) 3*√2ab²*(-a do piątej √3)=
3√2ab²(-a⁵×√3)